Transforming Decision-Making Process: A Research on the Impact and Quality of Decision-Making Related to Organizational Performance - Anil, Elizabeth (Digital Repository of Theses - SSBM Geneva, 2024)
Title: Transforming Decision-Making process: A Research on the impact and quality of Decision Making. A Comprehensive Evaluation of Decision-Making Process Quality. Effective decision-making is crucial to the performance and sustainability of organisations in a variety of industries. This study seeks to investigate and assess the quality of the decision-making process within organisations, putting light on the elements that influence decision-making outcomes and proposing improvement solutions. The study takes a multifaceted approach, drawing on ideas from organisational psychology, management theory, and data analytics. The research technique combines qualitative and quantitative methodologies, such as interviews with important stakeholders, decision-maker surveys at various levels, and historical decision data analysis. This study aims to find similar patterns, obstacles, and best practices in decision-making processes across various organisational contexts. Information is an important aspect that influences the quality of decision-making. Key factors influencing decision-making quality, such as information availability, communication dynamics, cognitive biases, and organizational culture, will be thoroughly examined. Special attention will be given to the role of emerging technologies, such as artificial intelligence and machine learning, in augmenting or hindering decision-making processes. The findings of this research aim to contribute valuable insights to both academic literature and practical organizational management. Recommendations for optimizing decision-making processes will be presented, taking into consideration the dynamic and evolving nature of today's business environment. Ultimately, the goal is to enhance the overall quality of decision-making within organizations, fostering innovation, adaptability, and sustained success in an ever-changing global landscape.